Fear of Terrorism in Armenia: Anxiety, Moral Panic and the Role of the Media - Balasanyan, Gurgen (2017)
In the aftermath of 9/11, terrorism has become a prominent area of research across multiple disciplines. Recent polls and surveys in the USA, Europe, and other countries directly affected by terror attacks show a substantial increase in the level of fear of terrorism. However, there is lack of research on the phenomenon in countries that do not have a recent history of terror attacks, nor are militarily involved in the global war on terror. The findings of this cross-sectional exploratory study are based on an online survey with 419 (N=419) respondents in one such terrorism-neutral country, Armenia. By applying the moral panic and terror management theories, the study analyzes sources of fear of terrorism, such as media, and the impact this fear has on the lives of the residents of the country. The results of the survey revealed that there is a considerable level of fear of terrorism in Armenia; however, the role of the media is minimized. It further found that those who experience higher level of fear of terrorism register a higher level of anxiety expressed through behavioral and emotional coping mechanisms. The study concludes with policy recommendations on how to mitigate the impact of terror attacks on the level of fear on a macro level, as well as presents suggestions and directions for future research